Cloning and Expression of Cockroach α7 Nicotinic Acetylcholine Receptor Subunit - Cartereau, Alison; Taillebois, Emiliane; Selvam, Balaji; Martin, Carine; Graton, Jérôme; Le Questel, Jean-Yves; Thany, Steeve H. (Frontiers in Physiology, 2020)
Understanding insect nicotinic acetylcholine receptor (nAChR) subtypes is of major interest because they are the main target of several insecticides. In this study, we have cloned a cockroach Pamealpha7 subunit that encodes a 518 amino acid protein with futures typical of nAChR subunit, and sequence homology to alpha7 subunit. Pamealpha7 is differently expressed in the cockroach nervous system, in particular in the antennal lobes, optical lobes and the mushroom bodies where specific expression was found in the noncompact Kenyon cells. In addition, we found that cockroach Pameα7 subunits expressed in Xenopus laevis oocytes can assemble to form homomeric receptors. Electrophysiological recordings using the two-electrode voltage clamp method demonstrated that nicotine induced an Imax current of -92 ± 27 nA at 1 mM. Despite that currents are low with the endogenous ligand, ACh, this study provides information on the first expression of cockroach alpha7 homomeric receptor.